1992
DOI: 10.1029/92pa02090
|View full text |Cite
|
Sign up to set email alerts
|

River Fluxes of Dissolved Silica to the Ocean Were Higher during Glacials: Ge/Si In Diatoms, Rivers, and Oceans

Abstract: Two centric marine diatom species, Thalassiosira oceanica and Thalassiosira antarctica, were grown in batch cultures to determine the incorporation of germanium (Ge) and silicon (Si) into siliceous shells (opal). The results were modeled as Ge/Si “isotope” fractionation. During exponential growth, diatoms take up and incorporate Ge/Si from solution without major discrimination against Ge. During stationary phase growth near silica limitation, the Antarctic species (T. antarctica) discriminates slightly against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
190
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(200 citation statements)
references
References 37 publications
7
190
2
1
Order By: Relevance
“…Chillrud et al (1994) have published the only glacial meltwater Ge/Si ratio to date. A maximum ratio of 1.35 pmol/Amol is given, which is more than double that of the global average riverine Ge/Si of 0.6 pmol/Amol (Froelich et al, 1992). With an increase in the runoff of glacial meltwater during the main period of deglaciation (7 -12 ka BP), there is a possibility that these higher ratios would increase the corresponding ratios within the oceans.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Chillrud et al (1994) have published the only glacial meltwater Ge/Si ratio to date. A maximum ratio of 1.35 pmol/Amol is given, which is more than double that of the global average riverine Ge/Si of 0.6 pmol/Amol (Froelich et al, 1992). With an increase in the runoff of glacial meltwater during the main period of deglaciation (7 -12 ka BP), there is a possibility that these higher ratios would increase the corresponding ratios within the oceans.…”
Section: Introductionmentioning
confidence: 89%
“…Ge/Si ratios within opals derived from deep ocean cores (Mortlock et al, 1991) vary on glacial to interglacial time scales. Froelich et al (1992) and Bareille et al (1998) have shown that these ratios within the opal faithfully record those of the ocean at the time they were formed. Primary controls on Ge/Si ratios within the oceans may include terrestrial chemical weathering intensity (Froelich et al, 1992), but more recent work suggests that diagenetic effects (Hammond et al 2000;King et al, 2000) and the preferential weathering of minerals with high Ge/Si ratios, particularly biotite (Filippelli et al, 2000), are probably more important.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ocean inventory of H4SiO 4 is determined by the balance between influx by weathering and removal by burial. There has been a suggestion, based on the germanium to silica ratio of sedimentary diatoms, that the global rate of silica delivery to the oceans from chemical weathering might have been higher during glacial time, perhaps because of the abrasive exposure of igneous rocks by ice sheets [Froelich et al, 1992]. Another possibility is that the riverine flux of H4SiO 4 is better able to reach the ocean during glacial time because of the lack of estuaries.…”
Section: Can We Monkey With the Glacial No• Inventory? An Astonishingmentioning
confidence: 99%